Integrating decision tools for the sustainable management of land contamination - Pollard, Simon J. T.; Brookes, Adam; Earl, N.; Lowe, J.; Kearney, T.; Nathanail, C. Paul (Elsevier Science B.V., Amsterdam., 2004)
The approach to taking decisions on the management of land contamination has changed markedly over 30 years. Change has been rapid with policy makers and regulators, practitioners and researchers having to keep pace with new technologies, assessment criteria and diagnostic methods for their measurement, techniques for risk analysis and the frameworks that support decision-makers in their efforts to regenerate historically contaminated land. Having progressed from simple hazard assessment through to ‘sustainability appraisal’ we might now consider piecing together the experience of decision-making for managing land contamination. Here, we critically review recent developments with a view to considering how better decisions can be made by integrating the decision tools available. We are concerned with the practicality of approach and the issues that arise for practitioners as decision criteria are broade
Keywords: Land contamination; Decision-making; Sustainable development; Risk-based land management